Adherence to Trust Section 17 Leave Policy at High Dependency Unit and an Open Rehab Unit - Heba Salem; Nidhi Gupta (BJPsych Open, 2025)
Aims: Following initial audit on trust policy for section 17 leave in 2023, this second cycle aimed to reassess staff adherence with the trust section 17 leave policy as well as monitor the change in practice. The first cycle of audit was presented at the clinical forum, and all the professionals agreed about documentation of reflections on leave and urine drug screen (UDS) in electronic notes.